Inflammation in Parkinson's disease: Role of glucocorticoids - Maria Trinidad eHerrero; Cristina eEstrada; Layal eMaatouk; Sheela eVyas (Frontiers Media S.A., 2015)
Chronic inflammation is a major characteristic feature of Parkinson's disease (PD). Studies in PDpatients show evidence of augmented levels of potent pro-inflammatory molecules e.g. TNF-α, iNOS,IL-1β whereas in experimental Parkinsonism it has been consistently demonstrated that dopaminergicneurons are particularly vulnerable to activated glia releasing these toxic factors. Recent geneticstudies point to the role of immune system in the etiology of PD, thus in combination withenvironmental factors, both peripheral and CNS-mediated immune responses could play importantroles in onset and progression of PD. Whereas microglia, astrocytes and infiltrating T cells are knownto mediate chronic inflammation, the roles of other immune-competent cells are less well understood.Inflammation is a tightly controlled process. One major effector system of regulation is HPA axis.Glucocorticoids released from adrenal glands upon stimulation of HPA axis, in response to either cellinjury or presence of pathogen, activate their receptor, GR. GR regulates inflammation both throughdirect transcriptional action on target genes and by indirectly inhibiting transcriptional activities oftranscriptional factors such as NF-kB, AP-1 or interferon regulatory factors. In PD patients, the HPAaxis is unbalanced and the cortisol levels are significantly increased, implying a deregulation of GRfunction in immune cells. In experimental Parkinsonism, the activation of microglial GR has a crucialeffect in diminishing microglial cell activation and reducing dopaminergic degeneration. Moreover,glucocorticoids are also known to regulate human brain vasculature as well as blood brain barrierpermeability, any dysfunction in their actions may influence infiltration of cytotoxic moleculesresulting in increased vulnerability of dopamine neurons in PD. Overall, deregulation ofGR actions is likely important in dopamine neuron degeneration throughestablishment of chronic inflammation.